2021
DOI: 10.1111/1759-7714.13928
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA FAM83A‐AS1 promotes lung adenocarcinoma progression by enhancing the pre‐mRNA stability of FAM83A

Abstract: Background Lung cancer is the leading cause of cancer deaths worldwide. Long non‐coding RNAs (lncRNAs) affect a series of cellular biological processes, including oncogene function promotion. In this study, we explored the functions and mechanisms of FAM83A antisense RNA 1 (FAM83A‐AS1) in non‐small cell lung cancer (NSCLC) progression. Methods The expression of FAM83A‐AS1and FAM83A mRNA was analyzed using the Cancer Genome Atlas (TCGA) data. Proliferation, migration, invasion and Western blotting were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…AF131215.5 also represented the independent prognostic significance of OS in patients with LUAD ( Hou and Yao, 2021 ). FAM83A-AS1 could increase FAM83A expression by enhancing FAM83A pre-mRNA stability and promote the tumorigenesis of LUAD ( Wang et al, 2021 ). FAM83A-AS1 was also verified to contribute to LUAD proliferation and stemness via the HIF-1α/glycolysis axis ( Chen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…AF131215.5 also represented the independent prognostic significance of OS in patients with LUAD ( Hou and Yao, 2021 ). FAM83A-AS1 could increase FAM83A expression by enhancing FAM83A pre-mRNA stability and promote the tumorigenesis of LUAD ( Wang et al, 2021 ). FAM83A-AS1 was also verified to contribute to LUAD proliferation and stemness via the HIF-1α/glycolysis axis ( Chen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…As discovered by Xiao et al, FAM83A-AS1 promotes the development of LUAD by regulating MMP14 expression and binding to miR-150-5p [ 53 ]. In addition, FAM83A-AS1 may also strengthen the pre-mRNA stability of FAM83A to improve the metastatic ability of lung adenocarcinoma [ 54 ]. In esophageal cell squamous carcinoma, FAM83A-AS1 downregulation regulates the miR-214/CDC25B axis to suppress tumor cell growth, invasion and migration [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al. ( 48 ). determined that FAM83A-AS1 upregulated FAM83A by enhancing the stability of FAM83A pre-mRNA, and promoted tumorigenesis of lung adenocarcinoma (LUAD).…”
Section: Discussionmentioning
confidence: 99%
“…found that STXBP5-AS1, an antioncogene, suppressed the expression of STXBP5 in non-small cell lung cancer (NSCLC) by blocking PI3K/ AKT, thereby inhibiting the progression of NSCLC. Wang et al (48). determined that FAM83A-AS1 upregulated FAM83A by enhancing the stability of FAM83A pre-mRNA, and promoted tumorigenesis of lung adenocarcinoma (LUAD).…”
Section: Discussionmentioning
confidence: 99%